The Ethics of Unlocking a Billion More Brains - Melody M. Thompson; Jinjie Wang (Adult Education Research Conference, 2014)
Online programs that engage a global audience are often promoted as “democratizing” education worldwide. However, the ethics of expecting students globally to conform to Western academic values and processes is largely ignored. Until programs are designed and delivered with cultural intelligence and humility, their full value will be compromised.